2015
DOI: 10.1155/2015/617282
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Levels of Soluble CD30 in Ankylosing Spondylitis Patients and Its Association with Disease Severity-Related Parameters

Abstract: Soluble CD30 (sCD30), a transmembrane glycoprotein that belongs to the tumor necrosis factor receptor (TNFR) superfamily, has been shown to be associated with various pathological conditions. This study was designed to measure the levels of serum sCD30 in patients with ankylosing spondylitis (AS) and to evaluate the relationships between serum sCD30 levels and other disease severity-related indexes, including bath ankylosing spondylitis disease activity index (BASDAI), ankylosing spondylitis disease activity s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
3
0
1
Order By: Relevance
“…There are scarce data on the effect of ART on sCD30 [ 26 ]. Levels in our population were considerably lower than those measured in the first 4 weeks of ART [ 48 ], and closer to levels published from HIV-negative volunteers [ 28 ]; however, sCD30 showed no independent association with virologic parameters. Levels of sCD14, IL-6, and cellular markers of immune activation in our study population were comparable to those previously measured in HIV-1-positive patients receiving ART for up to 6 years [ 19 , 49 ].…”
Section: Discussionsupporting
confidence: 74%
“…There are scarce data on the effect of ART on sCD30 [ 26 ]. Levels in our population were considerably lower than those measured in the first 4 weeks of ART [ 48 ], and closer to levels published from HIV-negative volunteers [ 28 ]; however, sCD30 showed no independent association with virologic parameters. Levels of sCD14, IL-6, and cellular markers of immune activation in our study population were comparable to those previously measured in HIV-1-positive patients receiving ART for up to 6 years [ 19 , 49 ].…”
Section: Discussionsupporting
confidence: 74%
“…We here identified a large number (40) of genes that have well-documented roles in the immune response, including for example TNFSF8/CD30L, interleukin-32 and several Th17-lymphocytes-related genes. TNFSF8 is a TNF-family member expressed on activated peripheral blood T-cells, B-cells, neutrophils, mast cells, monocytes, and macrophages and it is the ligand for CD30, a molecule that is present at high levels in AS patients compared to healthy controls [ 25 ]. The CD30/CD30L signaling system has been implicated in the pathogenesis of several autoimmune and inflammatory diseases and it has been recently associated to the pathogenesis of rheumatoid arthritis synovitis [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relatively high level of sCD30, whether statistically significant or not, in non-responders in our study may be related to this effect of biologic drugs. Disease-related factors could affect the level of sCD30; Gao et al reported that sCD30 level was significantly higher in AS [29] . Duzgun et al have reported the correlation between sCD30 and Behçet disease [30] .…”
Section: Discussionmentioning
confidence: 99%